Uma análise das percepções de professores sobre o uso da calculadora na resolução de problemas por estudantes com dificuldades de aprendizagem em matemática - Moraes, Andréia Dihl (2021)
This research aims to understand how teachers use the calculator in the classroom during problem-solving and what implications of its use for students with learning difficulties. Data collection was carried out through an online questionnaire, covering 100 teachers, of whom 50 teach mathematics in the early years of elementary school and the other 50, in the final years of elementary school and high school, working in 14 Brazilian states. The research has a qualitative character, which used the Discursive Text Analysis - DTA, as described by Moraes and Galiazzi (2011). Based on the data analysis, it was possible to observe the teachers' perceptions about problems, mathematical problems, types of problems, difficulties and learning disorders, types of difficulties perceived in students, as well as the contributions and disadvantages of using the calculator in solving problems used by students with learning difficulties. The results show that teachers who use problems in the classroom, usually use conventional problems even pointing out the use of unconventional problems and problem situations. It shows that they perceive some learning difficulties in their students, punctuating those related to learning disorders, development of strategies, reading and textual understanding, identification of data and operations and difficulty in establishing relations between Mathematics and reality. In addition to these results, he points out that the use of the calculator facilitates the student's learning in general, assists in the verification of results, allows reflection and creation of strategies as well, optimizes the resolution time in solving problems. In relation to students with learning difficulties, there is an increase in self-esteem, the inclusion of the student in the group, the encouragement of creativity, the help in understanding concepts, the increase in student motivation and performance, the aid to recognition the mathematical symbols, the development of critical sense, the reduction of stress in the face of Mathematics, in addition to providing the opportunity to handle the tool. To conclude the research, it is evident that the teachers who participated in this study do not usually use the calculator in the classroom, but understand that the use of the calculating machine in problem-solving contributes to students with learning difficulties.